Microscopy Applied to Biophotonics. - Pavone, F. S. (International School of Physics "Enrico Fermi.", 2014)
Biophotonics and microscopy are highly inter-related fields in terms of both technological development and biomedical applications. Recent advances in microscopy have been paralleled by new opportunities for biophotonics, including the investigation and manipulation of biological phenomena using light and its application to biomedicine. This book contains papers from the Enrico Fermi International School of Physics on Microscopy Applied to Biophotonics, held in Varenna, Italy, in July 2011. The lectures spanned the basic science of imaging, through advanced microscopy techniques, to the state-